If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 25 = 15x + -25 Reorder the terms: 25 + 6x = 15x + -25 Reorder the terms: 25 + 6x = -25 + 15x Solving 25 + 6x = -25 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 25 + 6x + -15x = -25 + 15x + -15x Combine like terms: 6x + -15x = -9x 25 + -9x = -25 + 15x + -15x Combine like terms: 15x + -15x = 0 25 + -9x = -25 + 0 25 + -9x = -25 Add '-25' to each side of the equation. 25 + -25 + -9x = -25 + -25 Combine like terms: 25 + -25 = 0 0 + -9x = -25 + -25 -9x = -25 + -25 Combine like terms: -25 + -25 = -50 -9x = -50 Divide each side by '-9'. x = 5.555555556 Simplifying x = 5.555555556
| 4=-2x+5 | | 13x-17y=-19 | | 10x-19=6x+11 | | x=54/(6/8) | | 2x^4-2x^3+4x^2-8x-16=0 | | 6x+2-4=9-x+8 | | x+(x+19)=29 | | 4x-5+x=5+3x-1 | | 6x+39=13x-91 | | 73-8x=-7 | | 42+5x=7 | | 6+5x=-18+x | | 3x-3=-13x-33 | | (-130)/(-13) | | 4a+7a+19=3*12-4+(5*16)-5 | | 8x-13=x+5 | | 2x+5=7-10 | | 12a-6=5+2a | | (4x-1)(4x-1)=0 | | (8/x)-2 | | 6x^2+3=10 | | 6x-6w+3x+9y+3y+2w= | | 9m-12=77 | | 10(d+4)=90 | | 2a-12=19 | | 9x+37=100 | | 5x-16=20-x | | (50x^6/2y^6)/(625x^4/10y^4) | | C-3=11 | | 2u=28 | | a^4-2a^2+1= | | E=0.9Y |